Fast tonotopy mapping of the rat auditory cortex with a custom-made electrode array - Lindovský, Jiří; Pysaněnko, Kateryna; Popelář, Jiří; Syka, Josef (Physiological research, 2018)
We present a custom-made multielectrode array for the recording of evoked potentials during acute experiments in rats, which offers a quick and reliable estimation of the cortical tonotopy. The array consists of electrodes represented by insulated copper wires of 0.09 mm diameter fixed in epoxy resin in a 3 x 5 arrangement, with final impedances of 410-800 kOhm. The array was placed on the brain surface of anesthetized rats approximately at the location of the auditory cortex (AC) and the cortical evoked potentials (middle-latency responses, MLR) were elicited by a series of tone pips of different frequencies at 50 dB of sound pressure level (SPL) intensity. The frequency that evoked the highest MLR amplitude (best frequency, BF) was identified for each electrode. The obtained distribution of the BFs characterized the cortical tonotopy, and it correlated with the frequency selectivity of neurons recorded at the same positions by an extracellular microelectrode. Although the space resolution of the array did not allow for the identification of AC sub regions, the array proved to be a reliable tool for a quick estimation and prediction of areas of interest for the subsequent measurements of neurons by more precise techniques.
Keywords: akustická stimulace; sluchové korové centrum; implantované elektrody; krysa rodu Rattus; Animals; Rats, Long-Evans; Time Factors; časové faktory; Evoked Potentials, Auditory; Rats; Auditory Cortex; zvířata; potkani Long-Evans; Electrodes, Implanted; Acoustic Stimulation; Brain Mapping; sluchové evokované potenciály; mapování mozku